Activation of NRF2/ARE by isosilybin alleviates Aβ25-35-induced oxidative stress injury in HT-22 cells - Zhou, Jing; Chao, Gao; Li, YuLei; Wu, Min; Zhong, ShuZhi; Feng, ZunYong (Neuroscience letters, 2016)
•Isosilybin alleviates HT-22 cell oxidative stress injury induced by Aβ25-35.•Isosilybin inhibits the accumulation of ROS in HT-22 cells.•Isosilybin activates the NRF2-ARE signalling to eliminates the accumulation of ROS in HT-22 cells. Aβ-mediated oxidative stress damage is considered a direct cause of Alzheimer’s disease (AD). Therefore, drugs that have been developed to block oxidative stress are considered effective for AD treatment. Isosilybin is a flavonoid compound extracted from Silybum marianum, and it has been confirmed to have many pharmacological activities. This study aimed to verify that isosilybin could alleviate the Aβ25–35-induced oxidative stress damage in HT-22 hippocampal cells and to investigate the specific targets of isosilybin. A non-toxic dose of isosilybin significantly inhibited the production of reactive oxygen species (ROS), the release of malondialdehyde (MDA) and lactate dehydrogenase (LDH), and the Aβ25–35-stimulated reduction in total antioxidant capacity (T-AOC). Subsequent studies showed that isosilybin significantly increased the protein and mRNA expression of antioxidases, including heme oxygenase-1 (HO-1), glutathione S-transferase (GST), and aldo-keto reductases 1C1 and 1C2 (AKR1C2). Moreover, isosilybin stimulated the activity of an antioxidant-response element (ARE)-driven luciferase reporter gene. Further studies showed that isosilybin induced the expression of NFR-2 in a time- and dose-dependent manner and promoted its translocation to the nucleus. This result indicated that the antioxidant function of isosilybin might be achieved through the activation of NRF2/ARE signalling. Subsequent studies showed that the NRF2-specific agonist t-BHQ effectively inhibited ROS, MDA and LDH release and T-AOC reduction under Aβ25–35 stimulation. In addition, t-BHQ induced the expression of HO-1, GST, and AKR1C2, as well as the activity of ARE luciferase reporter plasmids. NRF2 siRNA blocked the antioxidative stress damage function of isosilybin. Therefore, NRF2 is likely to be a key mediator of isosilybin’s anti-Aβ25–35-mediated oxidative stress damage function. Overall, our results confirmed that isosilybin regulates the expression of HO-1, GST, and AKR1C2 through the activation of NRF2/ARE signalling, inhibiting ROS accumulation and ultimately alleviating Aβ25–35-induced oxidative stress damage in HT-22 cells.